Size-optimized nuclear-targeting phototherapy enhances the type I interferon response for "cold" tumor immunotherapy. (15th March 2023) - Zhang, Xiliu; Yi, Chen; Zhang, Lejia; Zhu, Xinyu; He, Yi; Lu, Huanzi; Li, Yiming; Tang, Yuquan; Zhao, Wei; Chen, Guosheng; Wang, Cheng; Huang, Siming; et al.
Abstract: There is growing interest in the effect of innate immune silencing in "cold" tumors, which always fail in the immune checkpoint blockade monotherapy using PD-L1 monoclonal antibodies (aPD-L1). Combination of aPD-L1 with photodynamic therapy, i.e., photoimmunotherapy, is a promising strategy to improve the mono immunotherapy. Nuclear-targeting nanoparticles could elicit a type I interferon (IFN)-mediated innate immune response and reverse the immunosuppressive microenvironment for long-term immunotherapy of "cold" tumors. Photosensitizers such as zinc phthalocyanine (ZnPc) have limited ability to target the nucleus and activate innate sensing pathways to minimize tumor recurrence. Additionally, the relationship between nanoparticle size and nuclear entry capacity remains unclear. Herein, graphene quantum dots (GQDs) were employed as aPD-L1 and ZnPc carriers. Three particle sizes (200 nm, 32 nm and 5 nm) of aPD-L1/ZnPc/GQD-PEG (PZGE) were synthesized and tested. The 5 nm nanoparticles achieved the best nuclear enrichment capacity contributing to their ultrasmall size. Notably, 5 nm PZGE-based photodynamic therapy enabled an amplification of the type I IFN-mediated innate immune response and could convert "immune-cold" tumors into "immune-hot" ones. Utilizing their size advantage to target the nucleus, 5 nm nanoparticles induced DNA damage and activated the type I IFN-mediated innate immune response, subsequently promoting cytotoxic T-lymphocyte infiltration and reversing negative PD-L1 expression. Furthermore, the nanoplatform we designed is promising for the effective suppression of distant oral squamous cell carcinoma. Thus, for the first time, this study presents a size design strategy for nuclear-targeted photo-controlled immune adjuvants and the nuclear-targeted phototherapy-mediated immunomodulatory functions of type I IFN innate immune signalling for "immune-cold" tumors. Statement of Significance: The potential of commonly used photosensitizers to activate innate sensing pathways for producing type I IFNs is limited due to the lack of nuclear targeting. Facilitating the nuclear-targeting of photosensitizers to enhance innate immune response and execute long-term tumor killing effect would be a promising strategy for "cold" tumor photoimmunotherapy. Herein, we report an optimal size of PZGE nanoparticles that enable the nuclear-targeting of ZnPc, which reinforces the type I IFN-mediated innate immune response, synergistically reversing "cold tumors" to "hot tumors" for effective primary and distant tumor photoimmunotherapy. This work highlights the marked efficacy of ultrasmall nuclear-located nanocarriers and offers new insight into "immune-cold tumors" via prominent innate immune activation mediated by nuclear-targeting photoimmunotherapy. Graphical Abstract: Image, graphical abstract